Analysis of Opportunities and Threats in Chicken Farming (Comparative Case Study of Farming in Indonesia and the United States) - Kurnia Kurnia; Daspar Daspar (Review of International Economic, Taxation, and Regulations, 2025)
This study aims to analyze the opportunities and threats in the poultry farming sector, particularly chicken farming, through a comparative case study between Indonesia and the United States. The poultry industry plays a crucial role in supplying animal-based protein, especially chicken meat and eggs, in both countries. In Indonesia, the industry faces various challenges such as limited technology, feed price fluctuations, livestock diseases, and weak integration between smallholder farmers and large-scale producers. However, significant opportunities exist alongside growing domestic demand, government support, and advancements in farming technology (Azizah et al., 2024; Ministry of Agriculture, 2024). On the other hand, the United States dominates the global poultry market with its highly integrated, efficient, and data-driven production systems (Shahbandeh, 2024). Using a comparative approach and literature review from official sources such as Statistics Indonesia and the Ministry of Agriculture, this research concludes that Indonesia holds substantial potential to strengthen its poultry industry through production modernization, supportive policies, and human resource development. Benchmarking with the U.S. poultry system is expected to provide strategic direction for the sustainable development of the national poultry sector.